Keratin-based peptide: biological evaluation and strengthening properties on relaxed hair - Fernandes, Margarida M. (2012)
A peptide based on a fragment of hair keratin type II cuticular protein, keratin peptide (KP), was studied as a possible strengthening agent for weakened relaxed hair. The peptide was prepared both in aqueous water formulation (WF) and organic solvent formulations (OF), to determine the effect of organic solvents on peptide interaction with hair and the differences in hair recovery. Both peptide formulations were shown to improve mechanical and thermal properties of weakened hair with peptide in OF showing the stronger effect. As a potential new hair care product, and so would necessitate contact with skin, the cytotoxicity and genotoxicity of the peptide were also evaluated through different methodologies (Alamar Blue assay, 2′-7′-dichlorofluorescein probe, cell morphology and growth and evaluation of DNA damage by an alkaline version of the comet assay) in skin fibroblasts. These tests are indicators of the potential of peptide to cause irritation on skin or to be carcinogenic, respectively. The peptide in WF did not cause cytotoxicity or genotoxicity in any of the concentrations tested. The presence of OF, however, induced a 20% decrease in cell viability in all of the range of concentrations used after 72-h incubation. Moreover, OF inhibited cell growth and was considered genotoxic at first contact with cells. The peptide was therefore considered a promising strengthening agent for hair and was shown to be innocuous when applied in WF.